Penerapan Model Pembelajaran Numbered Heads Together Untuk Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan Pada Siswa SD - Amrah Amrah; Suarlin Suarlin; Chailing Chailing (Universitas Negeri Makassar, 2017)
This research is a classroom action research conducted in two cycles with each cycle consisting of 2 meetings. Each cycle passes through several stages in each cycle, is planning, execution, observation and reflection. The purpose of this study is to determine the application of learning type Numbered Heads Together (NHT) to improve student learning outcomes of grade IV SD Inpres BTN IKIP II. The subjects of this study are the students of grade IV SD, amounting to 26 people. Data collection techniques used are the test results of student learning conducted at the end of the cycle, the observation sheet and reflection. The collected data were analyzed using quantitative and qualitative analysis. The result of quantitative analysis shows that there is an increase of learning outcomes seen from the average score of students' PKn learning outcomes are in the low category in cycle I while in cycle II is in very high category. Quantitatively there is an increase in the activity and motivation of students to learn PKn. In this approach the students themselves construct or discover themselves from the concept of the given material. The teacher in this study acts as a facilitator in providing guidance and scatfolding. So, learning turns into student centered learning. Based on the results of this study can be concluded that the learning of PKn through the application of learning type NHT can improve the results of learning PKn students of class IV SD.